The Visions of Dom Francisco de Quevedo Villegas - Quevedo, Francisco de, 1580-1645; L'Estrange, Roger, Sir, 1616-1704 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Visions of Dom Francisco de Quevedo Villegas" by Francisco de Quevedo is a satirical work written in the 17th century. This text explores themes of morality, social criticism, and the human condition through surreal dialogues and vivid imagery. The narrative style presents various characters, including a devil and a catchpole, engaging in witty exchanges that expose the corruption and folly of society. At the start of the narrative, the protagonist recounts his experience at a convent, where he becomes curious about an exorcism. He meets a friend who takes him to a concealed part of the church, where they observe a chaotic scene involving a man supposedly possessed by a devil. The devil, however, reveals that it is the man who possesses the devil, cleverly criticizing societal figures like the catchpole, who are as corrupt as any devil. This sets the tone for a series of contemplative and humorous dialogues, where deeper truths about human nature, justice, and the absurdities of societal norms are uncovered, suggesting a broader critique of 17th-century Spanish society. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Los_Sue%C3%B1os
Release date is 2013-01-24
Transcribed from the 1904 Methuen & Co. edition by David Price
Keywords: Satire; Spanish literature -- Translations into English